Von Willebrand Factor Mediates Pneumococcal Aggregation and Adhesion in Blood Flow - Jagau, Hilger; Behrens, Ina-Kristin; Lahme, Karen; Lorz, Georgina; Köster, Reinhard W.; Schneppenheim, Reinhard; Obser, Tobias; Brehm, Maria A.; König, Gesa; Kohler, Thomas P.; Rohde, Manfred; Frank, Ronald; et al. (Frontiers in Microbiology, 2019)
Streptococcus pneumoniae is a major cause of community acquired pneumonia and septicaemia in humans. These diseases are frequently associated with thromboembolic cardiovascular complications. Pneumococci induce the exocytosis of endothelial Weibel-Palade Bodies and thereby actively stimulate the release of von Willebrand factor (VWF), which is an essential glycoprotein of the vascular haemostasis. Both, the pneumococcus induced pulmonary inflammation and the thromboembolytic complications are characterized by a dysbalanced haemostasis including a markedly increase in VWF plasma concentrations. Here, we describe for the first time VWF as a novel interaction partner of capsulated and non-encapsulated pneumococci. Moreover, cell culture infection analyses with primary endothelial cells characterized VWF as bridging molecule that mediates bacterial adherence to endothelial cells in a heparin-sensitive manner. Due to the mechanoresponsive changes of the VWF protein conformation and multimerization status, which occur in the blood stream, we used a microfluidic pump system to generate shear flow-induced multimeric VWF strings on endothelial cell surfaces and analysed attachment of RFP-expressing pneumococci in flow. By applying immuno fluorescence visualization and additional electron microscopy, we detected a frequent and enduring bacterial attachment to the VWF strings. Bacterial attachment to the endothelium was confirmed in vivo using a zebrafish infection model, which is described in many reports and acknowledged as suitable model to study haemostasis mechanisms and protein interactions of coagulation factors. Notably, we visualized the recruitment of zebrafish-derived VWF to the surface of pneumococci circulating in the blood stream and detected a VWF-dependent formation of bacterial aggregates within the vasculature of infected zebrafish larvae. Furthermore, we identified the surface-exposed bacterial enolase as pneumococcal VWF binding protein, which interacts with the VWF domain A1 and determined the binding kinetics by surface plasmon resonance. Subsequent epitope mapping using an enolase peptide array indicates that the peptide 195YGAEIFHALKKILKS210 might serve as a possible core sequence of the VWF interaction site. In conclusion, we describe a VWF-mediated mechanism for pneumococcal anchoring within the bloodstream via surface-displayed enolase, which promotes intravascular bacterial aggregation.